Answer:
The answer is C
Step-by-step explanation:
First, let's solve the equation √(2x - 4) - x + 6 = 0:
√(2x - 4) - x + 6 = 0
Let's denote √(2x - 4) as y, then:
y - x + 6 = 0
y = x - 6
Now, we'll square both sides to eliminate the square root:
y^2 = (x - 6)^2
2x - 4 = x^2 - 12x + 36
0 = x^2 - 14x + 40
0 = (x - 4)(x - 10)
So, the solutions are x = 4 and x = 10.
Now let's go through the options:
A. There is only one solution: x = 4. The solution x = 10 is an extraneous solution. - This is incorrect because there are two solutions.
B. There is only one solution: x = 10. The solution x = 4 is an extraneous solution. - This is incorrect because there are two solutions.
C. There are two solutions: x = 4 and x = 10. - This is the correct statement as it accurately reflects the solutions of the equation.
D. There is only one solution: x = 10. The solution x = 0 is an extraneous solution. - This is incorrect because there are two solutions and x = 0 is not a solution mentioned in the calculation.